Pengaruh Pemanfaatan Media Video Youtube Terhadap Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Informatika Kelas VIII SMP Negeri 1 Painan - Nurhalizah, Sry Sherly; Hidayati, Abna; Novrianti, Novrianti; Rahmi, Ulfia (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Critical thinking in informatics learning is an important competency that needs to be developed in students. This study aims to investigate the effect of the use of YouTube video media on the improvement of critical thinking skills of grade VIII students of SMP Negeri 1 Painan. Through a quantitative approach with an experimental design, this study compares the critical thinking skills of students who receive learning with YouTube video media (experimental class) with students who receive conventional learning (control class). The research sample was taken at a simple random rate from the student population of grade VIII, namely class VIII.6 (experimental class) and class VIII.4 (control class). Data collection was carried out using a questionnaire that had been validated, consisting of 26 statements to measure critical thinking skills. Data analysis was carried out in two stages, namely descriptive analysis to describe data characteristics and inferential analysis using a t-test to test the average difference in critical thinking skills between the two groups. The results showed that the average score of critical thinking ability of students in the experimental class (95.56) was significantly higher than that of the control class (87.36) with a significance value of 0.001. This indicates that the use of YouTube video media is effective in improving students' critical thinking skills in informatics subjects